LEGAL ASPECTS OF THE DEVELOPMENT OF RUSSIAN CONSTITUTIONALISM - Vinogradova, Elena; Danilevskaia, Inna; Mukhlynina, Maria; Patiulin1, Georgii; Dyuzhilova, Olga (Revista Inclusiones, 2020)
The article is devoted to the analysis of legal aspects of the development of Russian constitutionalism. It is necessary to develop and improve conceptual ideas about the law so that the state can actively promote a legal ideology of constitutionalism containing moral potential. This implies the priority of individual rights and freedoms, separation of powers, political pluralism, and a high role of the court. The implementation of ideas and principles underlying any ideology is impossible without the existence of special subjects that guide society to achieve the tasks and goals defined by this ideology. The legal ideology as objectively existing and normatively fixed system of ideas, principles, and values predetermines the nature of the activity of the subjects. These subjects act as independent ideological institutions of Russian constitutionalism, as well as a set of norms, prescriptions, and requirements regulating a special kind of social relations, emerging in the sphere of establishment and recognition of ideology.